How video calls affect mimicry and trust during interactions. (24th April 2023) - Diana, Fabiola; Juárez-Mora, Oscar E.; Boekel, Wouter; Hortensius, Ruud; Kret, Mariska E.
Abstract : Many social species, humans included, mimic emotional expressions, with important consequences for social bonding. Although humans increasingly interact via video calls, little is known about the effect of these online interactions on the mimicry of scratching and yawning, and their linkage with trust. The current study investigated whether mimicry and trust are affected by these new communication media. Using participant-confederate dyads ( n = 27), we tested the mimicry of four behaviours across three different conditions: watching a pre-recorded video, online video call, and face-to-face. We measured mimicry of target behaviours frequently observed in emotional situations, yawn and scratch and control behaviours, lip-bite and face-touch. In addition, trust in the confederate was assessed via a trust game. Our study revealed that (i) mimicry and trust did not differ between face-to-face and video calls, but were significantly lower in the pre-recorded condition; and (ii) target behaviours were significantly more mimicked than the control behaviours. This negative relationship can possibly be explained by the negative connotation usually associated with the behaviours included in this study. Overall, this study showed that video calls might provide enough interaction cues for mimicry to occur in our student population and during interactions between strangers. This article is part of a discussion meeting issue 'Face2face: advancing the science of social interaction'.